PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KETERAMPILAN BERPIKIR KREATIF DAN HASIL BELAJAR SISWA KELAS X SMA NEGERI 1 PARIGI - Wahida, Ferawati (JSTT, 2015)
Study on the effect of project-based learning model towards creative thinking skills and learning outcomes of studentson Grade X at SMA Negeri 1 Parigi. This study aims to determine the effect of project-based learning model toward creative thinking skills and learning outcomes of studentson Grade X at SMA Negeri 1 Parigi. The method used was a quasi-experimental design with non-equivalent control group design.Data were analyzed using t-test and descriptivestatistical methods. Samples were class XE as the experimental group and class XF as the control group, respectively and each class consisted of 36 students determined by purposive sampling technique. The results showed that the application of project-based learning model effect a significant toward creative thinking skills and learning outcomes of students on chemistry. Students' response to project-based learning on Chemistry has shown good results. Project-based learning model can be applied to improve creative thinking skills and learning outcomes of students on Grade X at SMA Negeri 1 Parigi.